Certainty in Language Increases Consumer Engagement on Social Media. Issue 1 (February 2021) - Pezzuti, Todd; Leonhardt, James M.; Warren, Caleb
Brands regularly attempt to stimulate consumer engagement by posting messages on social media platforms (e.g., Facebook), but their messages are often ignored. How can managers write social media messages that engage consumers? The present research sheds light on how the language of brand messages influences consumer engagement. Text analyses of brand messages posted on Facebook and Twitter shows that brand messages that include words that express certainty (e.g., always, everything, forever) are associated with higher levels of consumer engagement (e.g., likes, comments, shares/retweets). The results of two controlled experiments demonstrate that messages expressing certainty increase engagement by influencing how consumers perceive brands. Specifically, expressing certainty makes brands seem more powerful, and perceptions of power exert a positive effect on engagement. In addition, the indirect effect of certainty on consumer engagement is stronger (weaker) among consumers with higher (lower) power distance beliefs. These results assist marketing managers by demonstrating how language influences consumer engagement on social media.